Facile preparation of SnS2 nanoflowers and nanoplates for the application of high-performance hybrid supercapacitors. (29th November 2022) - Bao, Enhui; Sun, Jiale; Liu, Yafei; Ren, Xianglin; Liu, Xiaohong; Xu, Chunju; Chen, Huiyu
Abstract: In this work, the SnS2 nanoflowers (SnS2 NFs) were solvothermally prepared in the solvent of ethanol, while SnS2 nanoplates (SnS2 NPs) were obtained through the identical conditions except for the solvent of water. The flowers were assembled with numerous nanosheets with very thin thickness, and the NPs exhibited hexagonal shape. When used as the battery-type electrode material for supercapacitors, the SnS2 NFs delivered a specific capacity of as high as 264.4 C g −1 at 1 A g −1, which was higher than the 201.6 C g −1 of SnS2 NPs. Furthermore, a hybrid supercapacitor (HSC) was assembled with the SnS2 as positive electrode and activated carbon (AC) as negative electrode, respectively. The SnS2 NFs//AC HSC exhibited a high energy density of 28.1 Wh kg −1 at 904.3 W kg −1, which was higher than the 24.2 Wh kg −1 at 844.3 W kg −1 of SnS2 NPs//AC HSC. Especially, when the power density was enhanced to the highest value of 8666.8 W kg −1, the NFs-based device could still hold 20.4 Wh kg −1 . In addition, both HSC devices showed an excellent cycling stability after 5000 cycles at 5 A g −1 . The present method is simple and can be extended to the preparation of other transition metal sulfides (TMSs)-based electrode materials with brilliant electrochemical performance for supercapacitors. Graphical abstract: The SnS2 nanoflowers and SnS2 nanoplates were prepared in an autoclave at 170 °C using ethanol and water as solvent, respectively. The SnS2 nanoflowers exhibited battery-type electrochemical response with a huge capacity of 264.4 C g −1 at 1 A g −1, higher than the 201.6 C g −1 of SnS2 nanoplates. The assembled SnS2 nanoflowers//AC hybrid supercapacitor delivered a high energy density of 28.1 W h kg −1 at the power density of 904.3 W kg −1 . Image 1 Highlights: SnS2 nanoflowers and nanoplates were prepared via different methods. A high capacity of 264.4 C g −1 at 1 A g −1 was obtained for SnS2 nanoflowers. 76.7% rate capability was reached with current density increasing from 1 to 10 A g −1 . The HSC device delivered an energy density of 28.1 W h kg −1 at 904.3 W kg −1 .